2008
DOI: 10.1111/j.1365-2834.2007.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an intravenous medication infusion pump system: implications for nursing

Abstract: Infusion pumps are perceived by nurses to enhance safe nursing practice. Results stress the importance of management teams in sociotechnological transformations and their impact on job satisfaction among nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…) with nurses reporting that the devices enhanced their ability to provide quality nursing care (Bowcutt et al . ), increased nurses' self‐confidence (Bowcutt et al . , Rosenkoetter et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) with nurses reporting that the devices enhanced their ability to provide quality nursing care (Bowcutt et al . ), increased nurses' self‐confidence (Bowcutt et al . , Rosenkoetter et al .…”
Section: Resultsmentioning
confidence: 99%
“…), increased nurses' self‐confidence (Bowcutt et al . , Rosenkoetter et al . ), reduced medication errors (Bowcutt et al .…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Even less information is available describing the unique challenges health systems encounter when attempting to establish a smart-pump CQI initiative, such as the inclusion of numerous and diverse practice sites (e.g., both urban and community acute care hospitals); the location of system facilities across an expanded geographic area; variations in facility leadership, policies, and educational programs; and the use of multiple smart-pump drug libraries.…”
Section: Problemmentioning
confidence: 99%
“…The findings reported here are from an IRB approved multiphase study that included pre-testing the perceptions of hospital staff nurses regarding the anticipated impact of pump technology implementation on life patterns and job satisfaction (Phase I) (Bowcutt, et al, 2008) and post-testing their perceptions of the actual impact (Phase II), as well as assessing the perceptions of nurse managers regarding the impact of the implementation of device pumps (Phase III). The study reported here is based on the findings of Phase II.…”
Section: Purposementioning
confidence: 99%